THE CONCEPT, TYPES, AND SYSTEM OF SOCIAL FACTORS NEGATIVELY AFFECTING THE ENFORCEMENT OF THE HUMAN RIGHTS TO EDUCATION (BASED ON THE ANALYSIS OF LEGAL REGULATION OF EDUCATION IN THE CAUCASUS FROM THE 19th CENTURY UNTIL NOW) - Trofimov, Maxim; Provodina, Olesya; Smirnov, Dmitry; Zasseyev, Dzambolat (Revista Inclusiones, 2020)
The right to education is the most important cultural right of a person. Legal regulation quality and guarantees of a human right to education largely determine the overall level of development of the individual, certain sectors of citizens, and the state in general. However, any right is influenced by various factors that either improve or worsen the quality characteristics of the implementation of a subjective human right. These factors are generated by both society and state policy. Social factors that adversely affect the implementation of the human right to education have a certain legal nature, i.e. they appear and exist because the conditions for their appearance and existence are determined by the legal acts in force in the field of education. Any state is obliged to take care of the development of education in its territory, as an indispensable condition for advancement, stability, and national security. At the same time, a certain state ideology can be traced in the educational policy.